Facebook as soft infrastructure: producing and performing community in a mixed tenure housing development. Issue 9 (21st October 2021) - Witten, Karen; Kearns, Robin; Opit, Simon; Fergusson, Emma
Abstract: Place-based community networks provide a resource that can be drawn on to protect and promote the wellbeing of residents. We investigate the role of social networking sites (SNSs) in community formation in a new master-planned, mixed tenure, affordable housing estate in Auckland, Aotearoa/New Zealand. Waimahia Inlet was developed by a consortium of Māori organizations and community housing providers. Community formation was an explicit developer goal with public spaces to encourage face-to-face interaction designed into the development and social infrastructure nurtured on site. New residents were invited to join a closed Facebook group, created and moderated by a residents' association set up by the developer. In-depth interviews with 38 residents between 2017/18 revealed synergies between residents' use of online and offline interactional spaces for producing and performing an engaged and supportive community. Neighbourhood networks contributed to strengthened attachment to place and sense of security by residents.